ANALISIS PENDAPATAN USAHATANI PADI SAWAH DI DESA TALIKURAN KECAMATAN SONDER KABUPATEN MINAHASA (Income Analysis of Rice Field in Talikuran Village Sonder District Minahasa Regency) - Willy Ferdy Geral Rumengan; Theodora M. Katiandagho; Jenny Baroleh (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
This study aims to analyze the income of rice farming in Talikuran Village, Sonder District, Minahasa Regency. The research was carried out from October to November 2021. The data collected in this study were in the form of primary data and secondary data. Primary data were obtained from direct interviews with rice farmers using a questionnaire. Secondary data were obtained from the Talikuran Village Office and partly from the internet. Thirty farmers were selected randomly from a population of 97 farmers.The results showed that rice farming was profitable for farmers because the income per hectare received by rice farmers in Talikuran Village was IDR 4,331,715.22 in one growing season with an R/C ratio of 1.24.